Water-dispersed thermo-responsive boron nitride nanotubes: synthesis and properties. (4th December 2015) - Kalay, Saban; Stetsyshyn, Yurij; Lobaz, Volodymyr; Harhay, Khrystyna; Ohar, Halyna; Çulha, Mustafa
Abstract: In this study, water-dispersed thermo-responsive boron nitride nanotubes (BNNTs) were prepared in a simple two-step process, where on the first step oligoperoxide was grafted via the interaction of amino groups (defects) of BNNTs with pyromellitic chloroanhydride fragments in oligoperoxide molecules. The second step involves N-isopropylacrylamide (NIPAM) graft polymerization 'from the surface' of oligoperoxide-functionalized BNNTs resulting in poly(N-isopropylacrylamide) (PNIPAM) coating. The pristine and functionalized BNNTs were characterized by thermogravimetric analysis, Fourier transform infrared spectroscopy, ultraviolet–visible spectrophotometry, dynamic light scattering, scanning electron microscopy and atomic force microscopy. PNIPAM-functionalized BNNTs exhibit excellent dispersibility in water and possess thermo-responsive properties. The water-dispersion of thermo-responsive PNIPAM-functionalized BNNTs can help their potential use in biomedical applications as 'smart' surfaces, nanotransducers and nanocarriers.